2011
DOI: 10.1016/j.jcma.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of cytokine expression in cirrhotic rats

Abstract: Cirrhosis development in BDL rats is associated with progressively enhanced expression of hepatic pro-inflammatory and anti-inflammatory cytokines, which is not in accord with the corresponding serum concentration. The circulating cytokine concentration may not totally reflect the hepatic expression level throughout the development of cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
3
14
1
Order By: Relevance
“…1 The study by Hsieh et al study is characterized by a systemic approach to evaluate the overall picture of hepatic and circulating cytokines, including IFN-g, TNF-a, IL-10 and TGF-b, during cirrhosis development. 2 Their study shows that cirrhosis development is associated with progressively enhanced hepatic pro-and anti-inflammatory cytokine expression in BDL rats. However, corresponding serum concentrations were not completely in accordance with hepatic cytokine expression in BDL rats.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…1 The study by Hsieh et al study is characterized by a systemic approach to evaluate the overall picture of hepatic and circulating cytokines, including IFN-g, TNF-a, IL-10 and TGF-b, during cirrhosis development. 2 Their study shows that cirrhosis development is associated with progressively enhanced hepatic pro-and anti-inflammatory cytokine expression in BDL rats. However, corresponding serum concentrations were not completely in accordance with hepatic cytokine expression in BDL rats.…”
mentioning
confidence: 96%
“…8 Hsieh et al observed that the trends for serum TNF-a changes were not consistent with those for hepatic TNF-a expression levels, which suggests that measurement of serum TNF-a cannot reflect hepatic TNF-a expression. 2 Previous studies revealed that hepatic IFN-g mRNA correlated with the degree of liver damage. 9 Natgonat et al reported that hepatic IFN-g mRNA expression was higher in liver biopsy specimens from patients with primary biliary cirrhosis than in normal control individuals.…”
mentioning
confidence: 99%
See 3 more Smart Citations